Aplikasi Remote Sensing dan Geographic Information System untuk Pemetaan Pengembangan Kawasan Wisata Agro di Desa Candikuning, Kecamatan Baturiti, Kabupaten Tabanan - FEBITA SAFERA PUTRI; INDAYATI LANYA; I GUSTI PUTU RATNA ADI (Fakultas Pertanian Universitas Udayana, 2023)
Application Remote Sensing and Geographic Information System for Mapping the Development of Agro Tourism Areas in Candikuning Village, Baturiti District, Tabanan Regency. Bali Province is one of the provinces in Indonesia which is famous for its tourism. One of the supporting sectors for tourism is the agricultural sector. One of the well-known agro tourism areas in Bali Province is the Bedugul tourist destination or administratively, namely Candikuning Village, Baturiti District, Tabanan Regency. The purpose of this study was to determine the level of potential tourist attractions in agro tourism areas, make plans for developing agro tourism areas, develop information systems for agro tourism areas and make maps of the distribution of potential tourist attractions in agro tourism areas. This study uses several methods, namely satellite image analysis methods, field surveys, weighting and scoring on each tourist attraction, classification of potential tourist attractions and designing an information system for agro-tourism areas. Based on the results of the study, the standard deviation value to determine the level of potential tourist attraction is 27,42348 with the division of 3 tourist attraction with high potential, 10 tourist attraction with medium potential and 7 tourist attractionwith low potential. From the level of potential tourist attraction in the agro-tourism area, a development plan for the agro-tourism area is needed using a SWOT analysis which produces 2 S-O plans, 1 W-O plan, 1 S-T plan and 1 W-T plan. Remote sensing applications and geographic information systems are very helpful in making maps of agro-tourism areas. In addition, the technology is capable of compiling an information system for tourist attractions in IT-based agro-tourism areas.